Development of ultra high performance fiber- reinforced concrete barge for wind turbine - Gyang, Lazarus Dachollom (2022)
Floating offshore wind turbines (FOWT) are considered the economically viable solution for installing wind turbines in waters greater than 60m deep. The barge is one of the floating structures developed for the FOWT. It has the simplest design, fabrication and installation in comparison to other FOWT like the semi-submersibles, Tension Leg Platforms and Spar buoys. In order to reduce the cost of FOWT, concrete has been utilized to reduce the capital and operational expenditure of steel. However, there are limiting factors to the construction of concrete FOWT, which form the basis of this project. Concrete has low tensile strength and susceptible to chemical attack and freezing temperatures. As a result, a larger wall section is required to combat the environmental conditions of the sea which results in higher energy consumption, large volume of construction materials, a weightier structure and more difficulty in massive production. Hence in this study, ultra high performance fiber reinforced concrete (UHPFRC) is used to develop a barge FOWT to support a 5MW wind turbine for a site at the Atlantic and Northern North Sea region offshore Scotland. According to extensive review of the literature conducted, UHPFRC material has shown better mechanical properties and more resistance to marine conditions in comparison to conventional reinforced cement concrete (RCC). Also, due to high strength of UHPFRC material, the thickness of structural element can be reduced which leads to less material consumption and easy manufacturing. Therefore, UHPFRC barge is developed and investigated in this study to support a FOWT. The considered Barge is square shaped (40m x 40m) with a moon pool at the center (10m x 10m). Analysis had been conducted using a finite element method to evaluate hydrodynamic motions and structural strength of the UHPFRC barge under different loading conditions and the results were compared to a conventional reinforced cement concrete barge. Also, experimental tests were performed to measure the stability of the UHPFRC barge small sized prototype subjected to water waves in the wave flume and compared with RCC barge small sized prototype. The hydrodynamic analysis results from the finite element analysis showed less pitch motions in the UHPFRC barge than the RCC barge in 7 out of the 12 design load cases (DLCs) considered. The roll motions were less than 50 in both barges with insignificant difference between them and the UHPFRC barge experienced 10% to 20% less heave motions than the RCC barge in all 12 DLCs. In the structural analysis, the UHPFRC barge experienced a maximum deformation of 14mm under the applied loads. From the experimental tests conducted on the UHPFRC and RCC barge small sized prototypes, the RCC barge had lower heel compared to the UHPFRC barge with a percentage difference of 10% - 70%. However, the RCC barge experienced severe green water load which could cause it to capsize. In overall, the UHPFRC barge proved to be more effective in achieving better hydrodynamic motions and stability for the barge FOWT in comparison to the RCC barge and should be considered as alternative to the RCC material